Apparent diffusion coefficient of pediatric cerebellar tumors: A biomarker of tumor grade?. Issue 12 (12th August 2013) - Poretti, Andrea; Meoded, Avner; Cohen, Kenneth J.; Grotzer, Michael A.; Boltshauser, Eugen; Huisman, Thierry A.G.M.
Abstract Background The role of diffusion weighted imaging (DWI) to reliably differentiate tumor types and grades in pediatric cerebellar tumors is controversial. We aimed to clarify the discrepancy reported in previous articles. Procedures We retrospectively evaluated the apparent diffusion coefficient (ADC) values of the enhancing, solid parts of cerebellar tumors and correlated the absolute tumor ADC values and cerebellar and thalamic ratios with histology in a cohort of children with cerebellar tumors. Results Twenty‐four children (12 females) were included in the study. The median age at pre‐surgical MRI was 10 years (range 29 days–18.5 years). Absolute ADC values (mean 1.49, SD 0.25 vs. 0.63 ± 0.18), cerebellar (2.04 ± 0.33 vs. 0.83 ± 0.25), and thalamic ratio (1.98 ± 0.35 vs. 0.79 ± 0.23) were significantly higher in low‐ than in high‐grade tumors (P < 0.0001). Absolute ADC values and cerebellar and thalamic ratios were significantly higher in low‐grade astrocytomas than in MBs. Overlap was seen for WHO grade II and III ependymomas. One hundred percent specific cutoff ADC values of >1.2 × 103 and <0.8 × 10−3 mm2/s were established for low‐ and high‐grade tumors. Conclusion ADC analysis of the solid, contrast enhancing components of pediatric cerebellar tumors may facilitate differentiation between various tumor histologies. Pediatr Blood Cancer 2013;60:2036–2041. © 2013 Wiley Periodicals, Inc.